2003
DOI: 10.2114/jpa.22.237
|View full text |Cite
|
Sign up to set email alerts
|

An Adult with Atopic Dermatitis and Repeated Short-term Fasting

Abstract: It has been reported that nutritional stress, such as short-term fasting and long-term energy restriction, has a suppressive effect on allergic dermatitis in experimental animals. Furthermore, clinical study has demonstrated a positive association between weight loss by low-energy diet and improvement in patients with atopic dermatitis. In this report, a 23-year-old female with atopic dermatitis received a treatment of repeated short-term fasting. 24-hour fasting was conducted once a week for a period of 20 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In fact, decrease in cholesterol by fasting improved skin symptoms in AD patients (Kimata, 2002). Moreover, decrease in cholesterol by vegetarian diet or short-term fasting improved skin symptoms of AD (Nakamura et al, 2003;Tanaka et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…In fact, decrease in cholesterol by fasting improved skin symptoms in AD patients (Kimata, 2002). Moreover, decrease in cholesterol by vegetarian diet or short-term fasting improved skin symptoms of AD (Nakamura et al, 2003;Tanaka et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…In a clinical study, a low-energy diet reduced inflammatory symptoms and oxidative damage in patients with atopic dermatitis (Kouda et al, 2000). A case of a patient with atopic dermatitis and repeated one day fasting has also been reported (Nakamura et al, 2003). Furthermore, rapid and sustained beneficial effects of alternate-day calorie restriction in overweight adults with asthma have been recently reported (Johnson et al, 2007).…”
mentioning
confidence: 99%
“…Some authors reported the effects of low calory diets in adult AD. According to the results of Nakamura et al [21] and Tanaka et al [22] low calory diet resulted the improvement of skin symptoms: itching, and the sleep disturbance becoming milder. A significant decrease of the SCORAD index, LDH5 activity, eosinophil number, peripherial NK activity and neutrofil number and PGE2 synthesis of monocytes was shown.…”
Section: Discussionmentioning
confidence: 96%